Customer Satisfaction Pakcoy Attributes at Rumah Buah Tirtayasa Bandung - Febiola, Audia; Sadeli, Agriani Hermita; Hapsari, Hepi; Utami, Hesty Nurul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Pakcoy is one of the vegetable commodities sold at Rumah Buah Tirtayasa that has experienced sales that have not been on target for more than a year so Rumah Buah Tirtayasa needs to know the reason consumers buy pakcoy, the level of compatibility between the level of performance and the level of importance, and the level of consumer satisfaction after buying pakcoy at Rumah Buah Tirtayasa. The research design used was a quantitative design with a total of 67 respondents. This research uses descriptive analysis methods, Importance Performance Analysis, and Customer Satisfaction Index analysis. The results showed that (1) The characteristics of consumers of pakcoy products at Rumah Buah Tirtayasa are women aged early adulthood, namely 26-35 years who are married with income above the current UMR Bandung City of Rp 4,068,462 who work as private employees. Tirtayasa Fruit House pakcoy consumers buy and consume pakcoy for household needs and the majority of consumers have three family members. (2) Based on the results of the IPA calculation, the attributes that have been satisfactory are color, quality, price suitability with quality, availability, and taste, while the attributes whose performance needs to be improved are size, brand variation, packaging, and labels. (3) CSI's calculation results show that pakcoy consumers at Rumah Buah Tirtayasa are very satisfied with the performance of pakcoy attributes at Rumah Buah Tirtayasa. Companies must improve, innovate, improve performance, and educate consumers about the attributes that need to be improved. For future research, it is expected to examine more detailed attributes or use other variables related to consumer satisfaction.